Abiotic and Biotic Stress in Plants - Recent Advances and Future Perspectives 2016
DOI: 10.5772/62159
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Breeding for Resistance to Abiotic and Biotic Stresses

Abstract: Due to a specific structure of its main organs (root, stem, leaves, and head), sunflower can be successfully grown on marginal soils and in semiarid conditions, and it is more resistant to abiotic stresses, than other field crops. Unfortunately, it is very sensitive to biotic stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…In major crops (cereals) some of the central genes for drought tolerance have been identified, and furthermore, several of these genes have been integrated into the genome of cultivated varieties [37,38]. For sunflower, however, in sunflower, only H. argophyllus has been extensively studied for drought tolerance [23,39]. Frequently when wild relatives are used in breeding programs, the resulting progeny display reduced total yield, and these yields are also of a lower quality [40].…”
Section: Discussionmentioning
confidence: 99%
“…In major crops (cereals) some of the central genes for drought tolerance have been identified, and furthermore, several of these genes have been integrated into the genome of cultivated varieties [37,38]. For sunflower, however, in sunflower, only H. argophyllus has been extensively studied for drought tolerance [23,39]. Frequently when wild relatives are used in breeding programs, the resulting progeny display reduced total yield, and these yields are also of a lower quality [40].…”
Section: Discussionmentioning
confidence: 99%
“…tuberosus , and H . pauciflorus have also shown resistance in field tests (Škorić, 2016). Stafford and Thompson (1983) released a parental line, HA 207, resistant to charcoal rot based on a wild H. annuus from north Texas that is also rust resistant.…”
Section: Biotic Traitsmentioning
confidence: 99%
“…In the last three decades Phomopsis brown stem canker has become the most destructive disease worldwide (Škorić, 2016). Cuk (1982) reported that wild annual H .…”
Section: Biotic Traitsmentioning
confidence: 99%
“…However, total immunity has not been found in sunflower, and all improvement strategies rely on genomic tools such as molecular markers [ 3 ]. In this regard, the genetic basis of SHR resistance has been described as consisting of many genes of small quantitative effects whose expressions are highly dependent on the environment with different mechanisms involved in resistance at each phase of the disease in sunflower [ 4 ].…”
Section: Introductionmentioning
confidence: 99%